PENINGKATAN KOMPETENSI GURU DALAM MENERAPKAN PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR - Imas Srinana Wardani; Akhmad Qomaru Zaman; Prayogo; Yustitia, Via; Amelia Widya Hanindita (Universitas PGRI Adi Buana Surabaya, 2024)
This community service activity aims to provide training on differentiated learning and the preparation of teaching modules at UPT Gugus 2 SDN Sampangagung 1 Mojokerto, East Java. This training was attended by 30 elementary school teachers. The methods used included presentations, group discussions, and the preparation of teaching modules. Participants were enthusiastic and highly committed to improving their skills. The results of this training showed an increase in teachers' understanding of differentiated learning and the ability to prepare teaching modules that are more varied and in accordance with student characteristics. This training is expected to contribute to improving the quality of learning. This activity went smoothly thanks to the good cooperation between the implementation team, the school, and the participants. This training can be a model for other schools in an effort to improve the quality of education through a more personal and innovative approach.